Blood and Sand Based on a Novel by Vicente Blasco Ibáñez - Sauer, Rodney (Kino Lorber, 2020)
Juan Gallardo (Valentino), a village boy born into poverty, grows up to become one of the greatest matadors in Spain. He marries a friend from his childhood, the beautiful and virtuous Carmen (Lee), but after he achieves fame and fortune he finds himself drawn to Doña Sol (Naldi), a wealthy, seductive widow. They embark on a torrid affair with sadomasochistic overtones, but Juan, feeling guilty over his betrayal of Carmen, tries to free himself of Doña Sol. Furious at being rejected, she exposes their affair to Carmen and Juan's mother, seemingly destroying his marriage. Growing more and more miserable and dissipated, Juan becomes reckless in the arena. He is eventually killed in a bullfight but does manage to reconcile with Carmen moments before he dies. [wikipedia.org]
Keywords: Blu-Ray-Disc